Asupan Lemak dengan Rasio Lingkar Pinggang Panggul pada Mahasiswa STIKES Wira Husada di Sleman Yogyakarta - Siti Uswatun Hasanah; Prastiwi Putri Basuki; STIKES Wira Husada Yogyakarta (HB PRESS, 2013)
Adolescents are a group to watch the intake of nutritional health, especially because, in adolescence, physiological changes occur so that the energy and nutrient needs are very influential on the growth and development of adolescents. quality aspects of adolescent health, nutritional status, and achievement of learning as a form of juvenile productivity in turn will affect the quality resources. Students are pubescent and adolescent group adolesens, and is still a lack of research on adolescents. Therefore, researchers interested in studying about the intake of fat with waist circumference ratio pelvis on students in STIKES Wira Husada in Sleman, Yogyakarta. This study is a descriptive cross sectional analytic approach. The sample of 120 people was taken by purposive sampling, the data were analyzed with the Spearman Rank. The average age of respondents was 21,62-2,11 years. Of the 120 respondents consisted of 50,8% were male and 49,2% female. Energy intake of 60,8% of respondents in both categories, and for fat intake of 120 respondents 31,7% in the low category. Circumference Waist Hip Ratio of 120 respondents 67,5% had obese category, with an average of 71,04 and a waist circumference hip circumference average of 81,29. From the research value of 0,307 significancy then there is no relationship between fat intake ratio of waist circumference to hip circumference. Conclusion: There is no relationship between fat intake ratio of waist circumference to hip circumference.